Spectacular Power in the Early Han and Roman Empires - Robinson, Rebecca (Journal of World History, 2018)
During their long reigns, Emperor Wu of the Western Han and Augustus of Rome respectively performed two spectacular ceremonies, the feng and shan sacrifices and the ludi saeculares. The performance of these ceremonies took place during a larger process of reforms to each state’s religious institutions and marked the culmination of these reforms. While there is no direct connection between the two rulers or their respective ceremonies, some of the salient characteristics can be compared. In both cases, the rulers claimed to revive ancient ceremonies, but incorporated new narratives of rulership into their performance. These spectacular ceremonies, performed in front of audiences, demonstrated the exalted position of the ruler, as well as the acceptance of the elites to the new order.

Imperial Cults: Religion and Politics in the Early Han and Roman Empires - Robinson, Rebecca (Oxford University Press, 2023)
Imperial Cults is a comparative study of the transformation of imperial religion and imperial authority in the early Han and Roman empires. During the reigns of the Emperor Wu of Han and Octavian Augustus of Rome, the rulers undertook substantial reforms to their respective systems of cult, at a time when they were re-shaping the idea of imperial authority and consolidating their own power. The changes made to religious institutions during their reigns show how these reforms were a fundamental part of the imperial consolidation. Employing a comparative methodology the author discusses some of the common strategies employed by the two rulers in order to centre religious and political authority around themselves. Both rulers incorporated new men from outside of the established court elite to serve in their religious institutions and as advisors, thus weakening the authority of those who had traditionally held it. They both expanded the reach of their imperially-sponsored cult, and refashioned important ceremonies to demonstrate and communicate the unprecedented achievements of each ruler. Emperor Wu recruited experts in mantic knowledge from far reaches of the empire, while Augustus co-opted loyal followers into the newly revived priestly colleges. Robinson shows how the rulers used their respective religious institutions to consolidate their authority, secure support, and communicate their authority to the elite and commoners alike. By using the comparative approach, the author not only reveals similar trends in the formation of ancient empires, but also shows how new perspectives on familiar material can be found when engaging with other societies. , Imperial Cults is a comparative study of the transformation of imperial religion and imperial authority in the early Han and Roman empires. During the reigns of the Emperor Wu of Han and Octavian Augustus of Rome, the rulers undertook substantial reforms to their respective systems of cult, at a time when they were re-shaping the idea of imperial authority and consolidating their own power. The changes made to religious institutions during their reigns show how these reforms were a fundamental part of the imperial consolidation. Employing a comparative methodology the author discusses some of the common strategies employed by the two rulers in order to centre religious and political authority around themselves. Both rulers incorporated new men from outside of the established court elite to serve in their religious institutions and as advisors, thus weakening the authority of those who had traditionally held it. They both expanded the reach of their imperially-sponsored cult, and refashioned important ceremonies to demonstrate and communicate the unprecedented achievements of each ruler. Emperor Wu recruited experts in mantic knowledge from far reaches of the empire, while Augustus co-opted loyal followers into the newly revived priestly colleges. Robinson shows how the rulers used their respective religious institutions to consolidate their authority, secure support, and communicate their authority to the elite and commoners alike. By using the comparative approach, the author not only reveals similar trends in the formation of ancient empires, but also shows how new perspectives on familiar material can be found when engaging with other societies.

Technologies of the Self in Early China - Robinson, Rebecca (Association of Asian Studies, 2024)
Recent discoveries of legal and administrative documents from the Qin and early Han have allowed us to form a much better perspective on the systems these two states implemented to govern their land and people. Texts from sites such as Shuihudi, Zhangjiashan, Liye, in particular, shed much light on how the state attempted to keep track of its population, through an expansive bureaucratic system that kept census records and tied individuals to their place of residence. These technologies of governance strengthened the state and laid the foundations for subsequent bureaucratic systems. Integral to this system was the requirement that the people make their own individual census reports and aid the state in enforcing the laws through the system of linked liability. Anthony Barbieri-Low and Robin Yates’ recent publication Law, State, and Society in early Imperial China gives us a detailed overview of how the state used the legal system to govern the population. This presentation will investigate the alternate side of the topic, by looking at the people, rather than the state. Using similar source materials, particularly the legal statutes and the Book of Submitted Doubtful Cases from Zhangjiashan, my research looks at how these legal and social systems, particularly the census exercises, caused people to change their own behaviour, and how people shaped their identities through these systems. These individual attempts at governing the self functioned in tandem with the state bureaucracy, whether intentionally or not, to create a more governable population.

What Should the State Know? Theories of State Information Gathering in Early China - Robinson, Rebecca (Association of Asian Studies, 2023)
During the Warring States period, scholars and statesmen spent much time debati...

Cult and calendars in the ancient empires of Qin, Han, and Rome - Robinson, Rebecca (McGill University, 2017)
Cult and Calendars in the Ancient Empires of Qin, Han, and Rome is a comparison of reforms made to imperial cult and calendar during the formative years of empire. As distinct from ruler cult, I define imperial cult as cult activity worshiped both by the emperor and on his authority. The early years of the Qin Han and Roman empires saw imperially-sponsored cult increase dramatically, and saw the positioning of the person of the emperor at the centre of all cult activity. In both empires, reforms to state cult and calendars were initiated as part of a larger program of consolidating power around the person of the emperor. Despite the very different challenges facing the emperors of Han and Rome, there is a remarkable similarity in the areas in which they chose to consolidate their power, as well as the methods through which they carried out their reforms. In both empires, the rulers sought the advice of advisors from outside of the traditional elite, incorporating astronomical and religious knowledge from diverse regions and peoples. This outside knowledge and practices were then incorporated into state cult, reshaping the way that the emperors and their subordinates worshipped. I argue that these reforms to cult, and the incorporation of outside knowledge, was fundamental to the consolidation of power in the person of the emperor. Examining the expansion of cult practices, calendrical reforms, and spectacular performances, the dissertation uncovers the processes in the transformation of imperial cult to fit the changing needs of empire. Rather than seeking parallels in belief systems or cult practice, the dissertation compares the ways in which religious institutions both shaped and communicated a new imperial order. The juxtaposition of the two societies reveals not only the similarities and differences in these processes, but also the biases of historical sources and subsequent scholarship in both fields.